APAKAH LAPORAN KEUANGAN BERMANFAAT BAGI UMKM? PERAN KULTUR ORGANISASI DAN TEKNOLOGI INFORMASI - Cahyadi, Luh Diah Citra Resmi; Lasmini, Ni Nengah (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.08.NO.11.TAHUN 2019, 2019)
The purpose of this study was to determine the effect of organizational culture and information technology on the quality of SME financial statements in the Province of Bali, and to determine the effect of organizational culture, information technology and quality of financial reports on the quantity of credit received by SMEs in Bali Province. The sample of this study was 100 SMEs in the Province of Bali, where sampling using a simple random sampling technique. The results of this study are organizational culture variables that are not significant in influencing the quality of financial statements. Technological variables have a positive and significant impact on the quality of financial statements. Respondents were very helpful in preparing financial statements using financial statement preparation software. Organizational culture and technology variables do not significantly influence the quantity of credit received by SMEs. While the variable quality of financial statements has a positive and significant effect on the quantity of credit received by SMEs